The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1556/1646.8.2016.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-associated pneumonia and the importance of education of ICU nurses on prevention – Preliminary results

Abstract: Background and aimsVentilator-associated pneumonia (VAP) increases intensive care unit (ICU) length of stay, ICU mortality, the number of ventilator days, and costs. We implemented a VAP bundle and investigated its efficacy on prevention. Materials and methodsA prospective observational study was conducted between January 1, 2015 and December 31, 2015 in a 12-bed multidisciplinary ICU. The bundle was implemented on July 02, 2015. Comparative analysis was performed before and after the implementation of the bun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
11
0
2
Order By: Relevance
“…There was a rate of 88.81% in the post-intervention period for HH before the procedure and 94.88% after. These rates are similar to those reported by Lake Of The Woods District Hospital in Canada with 87.7% of adherence to HH before the intervention and 93.2% after the educational intervention (20) .…”
Section: Reduced Duration Of Patients To Daily Sedation Interruptionssupporting
confidence: 87%
“…There was a rate of 88.81% in the post-intervention period for HH before the procedure and 94.88% after. These rates are similar to those reported by Lake Of The Woods District Hospital in Canada with 87.7% of adherence to HH before the intervention and 93.2% after the educational intervention (20) .…”
Section: Reduced Duration Of Patients To Daily Sedation Interruptionssupporting
confidence: 87%
“…Obtaining VAP might be not only be via ventilator. Health workers especially nurses have an important role in inhibiting colonization of bacteria by mechanical ventilation (22). In the present study, 3 out of 4 S. aurous isolates were Methicillin-resistant S. aureus (MRSA).…”
Section: Discussionmentioning
confidence: 77%
“…The effect of compliance with the complex set of strategic procedures with a demonstrated effect upon a significant decrease of VAP incidence has a great impact upon decreasing the incidence of this disease, as has been confirmed with numerous studies performed at departments of intensive care (Álvarez-Lerma et al, 2014; Oliveira et al, 2014). As an example, it is possible to mention the study performed by Hungarian authors, which showed a decreased incidence of VAP and decreased relative risk of 44% following the introduction of the preventive bundle of measures (Mogyoródi et al, 2016). The basic and simplest measure in VAP prevention is keeping the patient in a semirecumbent position, which has a positive effect upon decreasing the incidence of VAP (Caserta et al, 2012; Dosher et al, 2014; El Azab et al, 2013).…”
Section: Discussionmentioning
confidence: 99%